HUBUNGAN PERAN KONSERVASI TERHADAP SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Sofia, Annissa Nur; Nugraheni, Nursiwi (Jurnal Samudra Geografi, 2024)
Conservation is an effort to protect or maintain natural resources so that damage does not occur. Conservation is an effort to preserve or protect resources that are processed wisely so that they obtain the maximum benefits and can be utilized for now and for future generations. Conservation activities are an inseparable part of sustainable development goals (SDGs). Conservation plays an important role in maintaining ecosystems, biodiversity, and can provide benefits in the economic, social and cultural fields. This article was prepared using a literature study method based on journal articles discussing conservation and its relationship with sustainable development goals (SDGs).